Método para retorno sobre investimento após a implantação de software - Paduam, Taísa Cordeiro (2015)
Currently organizations have been concerned with the analysis of the impact of IT investments. Economic pressures, combined with years of significant IT spending without demonstrating clear returns, forced companies to improve their financial practices and justify better and more clearly every penny invested way. Thus, this study presents the method to calculate the return on investment after software implantation. This method was generated from four experiments conducted in the laboratory and in the field, applied in southern Brazil, which showed effective action to catch the postdeployment time metrics. However, this study may be applicable to all companies wishing to calculate the temporal return from an Implantation.